TANTANGAN FONEMIS DALAM BIPA: REALISASI KONSONAN BAHASA INDONESIA OLEH PEMELAJAR AMERIKA - Astuti, Dewi Wahyuning; Indrayani, Lia Maulia; Erlina, Erlina (Jurnal Semantik, 2025)
This study investigates the articulatory challenges faced by 20 American BIPA learners in pronouncing Indonesian consonants. Employing a qualitative descriptive method, the research focuses on analyzing phonetic deviations based on recorded oral data. A total of 153 utterances were examined to identify patterns in consonant realizations. The findings reveal significant difficulties in articulating specific consonant phonemes, including bilabial plosives [b], [p], glottal fricatives [h], apico-alveolar plosives [d], [t], dorso-velar plosives [g], [k], lamino-palatal affricates [tʃ], and postalveolar affricates [dʒ]. The results demonstrate recurring phonological processes such as substitution, deletion, and addition of sounds. Substitution patterns include [t] realized as [tʃ] or [d] and [dʒ] as [tʃ]. Deletion frequently occurs in final consonants, particularly [h], [t], and [g]. Additionally, some learners added glides [tʃj] or modified articulations [ŋˈɡ], [dʒj] to accommodate unknown phonemes. This study emphasizes the need for targeted pronunciation training in BIPA programs, such as minimal pair analysis, word and sentence repetition, with a focus on consonant production accuracy through repetitive exercises and phonetic awareness activities. By addressing these challenges, BIPA teachers’ or instructors can be better in supporting learners to achieve more native-like pronunciation.